Przekształcenia w strukturze podmiotowej rynku ubezpieczeniowego w Polsce - Bednarczyk, Teresa H. (Transformations of the Subjective Structure of Insurance Market in Poland, 2008)
Polish insurance market is being continually changed because of the economic, political, technological, and social reasons. One of the indications of these transformations are the mergers and acqusitions and the unification of different sectors of the financial market. In the first part of this paper, there were presented the main changes in the subjective structure of insurance market in Poland, especially according to the conditions for the competitiveness and the range of market's concentration. The second part of this paper includes the characteristic of insurance market's consolidation. There were shown the main circumstances of consolidation, the meaning of foreign capital in these processes and also the objective scope of insurance groups' activity. The summary includes the synthetic conclusions.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1197, s. 22-29